IMPACT OF EXTRACTION SOLVENTS AND FRACTIONATION TECHNIQUES ON PHENOLIC CONTENT AND ANTIOXIDANT POTENCY IN TURMERIC (CURCUMA DOMESTICA) - Pratiwi, Denia; Wardaniati, Isna; Nasution, Azlaini Yus; Islami, Deri; Mardhiyani, Dini (Himpunan Perawat Medikal Bedah Indonesia (HIPMEBI) Regional Jawa Barat, 2024)
Turmeric is known to have many properties, one of which is as an antioxidant, the active substance which is considered to play a role in this activity is curcuminoid. Curcuminoids are part of the secondary metabolites of flavonoids and more specifically are phenolic. The purpose of this study was to examine the effect of the type of solvent on total phenolic levels with antioxidant activity in turmeric. The method of the research is experimental laboratory has been carried out at the FMIPA UNRI laboratory in 2019. The turmeric rhizome which has been made as a simplicial is extracted using ethanol and graded fractionated using n-butanol and ethyl acetate solvents. Determination of total phenolic levels with Follin Ciocalteau reagents using a Microplate reader and gallic acid comparison while the value of antioxidant activity using the DPPH method. The result will be analyzed descriptively. Based on the results of the study it was found that there is a solvent effect on total phenolic content and antioxidant activity seen from IC50 values and different total phenolics, namely in determining the total phenolic content of turmeric (Curcuma domestica) successively ethanol extract, water fraction, ethyl acetate fraction, fraction n-butanol of 90.1364; 22,0303; 45,2397; 20,9697 mg / g (GAE) and on the measurement of antioxidant activity the IC50 value was 65.7506 µg / mL; 384,2774 µg / mL; 64,6012 µg / mL; 834,3335 µg / mL with smaller activity compared to the antioxidant activity of vitamin C which is 7.27624 µg / mL.